2021
DOI: 10.20417/nzjecol.45.2
|View full text |Cite
|
Sign up to set email alerts
|

Bioacoustic monitoring of lower North Island bird communities before and after aerial application of 1080

Abstract: Woody plants in arid and semi-arid environments may enhance soil nutrient status, the so-called 'fertile island' effect, but this mechanism has never been tested in the drylands of New Zealand. In this study I investigated effects of Kunzea serotina, Discaria toumatou, Rosa rubiginosa, and Coprosma propinqua on soil properties in the drylands of central Otago, New Zealand. Soils had significantly higher organic matter under C. propinqua and significantly higher nitrate and phosphorus concentrations under K. se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a study on soil properties at three different altitudes in the Qilian Mountains, researchers showed that with the increase in altitude, the soil nutrition and microbial-biomass parameters mostly decreased, and the 'fertilizer island' effect increased (Zhao and An, 2021). In woody plants and shrub communities, such as Haloxylon ammodendron, Tamarix ramosissima, and Populus euphratica, the nutrient enrichment in the topsoil under the canopies was obvious, and the 'fertilizer island' effect in the upper soil layer was greater than that in the lower soil layer (Reynolds et al, 1999;Chen et al, 2018;Guo et al, 2020;Bomans et al, 2021). Researchers investigated the soil moisture, nutrient content, and fine root density, and they found that the interaction between plants and soil was important for the formation and development of fertile islands and that its influence was not only related to the soil surface but also extended to the depth of the root contact (Cao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a study on soil properties at three different altitudes in the Qilian Mountains, researchers showed that with the increase in altitude, the soil nutrition and microbial-biomass parameters mostly decreased, and the 'fertilizer island' effect increased (Zhao and An, 2021). In woody plants and shrub communities, such as Haloxylon ammodendron, Tamarix ramosissima, and Populus euphratica, the nutrient enrichment in the topsoil under the canopies was obvious, and the 'fertilizer island' effect in the upper soil layer was greater than that in the lower soil layer (Reynolds et al, 1999;Chen et al, 2018;Guo et al, 2020;Bomans et al, 2021). Researchers investigated the soil moisture, nutrient content, and fine root density, and they found that the interaction between plants and soil was important for the formation and development of fertile islands and that its influence was not only related to the soil surface but also extended to the depth of the root contact (Cao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%